High-thermal-conductivity buffer type organic silicon pressure-sensitive adhesive and preparation method thereof

By combining modified single-wall carbon nanotubes, single-layer graphene and aluminum nitride, the problem of insufficient thermal conductivity of traditional silicone pressure-sensitive adhesives is solved, and a high-thermal buffered silicone pressure-sensitive adhesive is prepared, which improves the heat diffusion ability and extends the service life of electronic products.

CN120555007APending Publication Date: 2025-08-29JIANGSU SIDIKE NEW MATERIALS SCI & TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510590704.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-08
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

Traditional silicone pressure-sensitive adhesives have low thermal conductivity and cannot disperse the heat generated by electronic products in time, resulting in heat accumulation and damage to electronic components and affecting product life.

Method used

Thermal conduction fillers such as modified single-wall carbon nanotubes, single-layer graphene, boron nitride and aluminum nitride are used to establish thermal conduction paths and improve thermal conductivity through the combination of tubular, sheet-like and spherical microstructures.

Benefits of technology

The preparation of high thermal buffered silicone pressure-sensitive adhesive is realized, which significantly improves the heat diffusion ability and extends the life of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120555007A_ABST
    Figure CN120555007A_ABST
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity buffer type organic silicon pressure-sensitive adhesive and a preparation method thereof, and the pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 90-150 parts of vinyl silicone rubber, 180-300 parts of methyl MQ silicon resin, 1.5-15 parts of hydrogen-containing silicone oil, 30-60 parts of a first thermal conductive filler, 40-80 parts of a second thermal conductive filler, 40-80 parts of a third thermal conductive filler and 1-5 parts of a catalyst. 1-5 parts of an inhibitor and 300-500 parts of a solvent. The linear structure of an organic silicon pressure-sensitive adhesive polymer molecule has flexibility and excellent buffering performance, but the thermal conductivity of the organic silicon pressure-sensitive adhesive polymer molecule is poor, and the general thermal conductivity is about 0.2 W / (m.K), so that the organic silicon pressure-sensitive adhesive is endowed with high thermal conductivity by utilizing a special filler treatment method and a special compounding method on the premise of considering the buffering performance of the organic silicon pressure-sensitive adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of organosilicon pressure-sensitive adhesive materials, and in particular to a high-thermal-conductivity buffer-type organosilicon pressure-sensitive adhesive and a preparation method thereof. Background Art

[0002] Silicone pressure-sensitive adhesives, based on silicone polymers, are currently the only pressure-sensitive adhesives capable of operating over a wide temperature range of -73°C to 300°C. Their backbone consists of Si-O bonds, while their side chains are organic groups, combining the advantages of both organic and inorganic materials. This unique structure imparts excellent resistance to acid and alkali corrosion, water, and weathering, as well as excellent high and low temperature resistance and biological inertness.

[0003] In recent years, silicone pressure-sensitive adhesives have been replacing traditional composite foam structures in 3C electronic products due to their excellent cushioning properties. They offer thinner thickness, simpler manufacturing, and lower cost. However, traditional silicone pressure-sensitive adhesives have extremely low thermal conductivity, making them unable to dissipate heat generated by electronic products in a timely manner. Heat accumulation damages electronic components, ultimately shortening the lifespan of electronic products. Therefore, improving their thermal conductivity and accelerating heat dissipation has become urgent. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a high thermal conductivity buffer type silicone pressure sensitive adhesive and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a high thermal conductivity buffer type silicone pressure-sensitive adhesive is provided, and the raw materials for its preparation include the following components by weight: 90-150 parts of vinyl silicone rubber, 180-300 parts of methyl MQ silicone resin, 1.5-15 parts of hydrogenated silicone oil, 30-60 parts of a first thermally conductive filler, 40-80 parts of a second thermally conductive filler, 40-80 parts of a third thermally conductive filler, 1-5 parts of a catalyst, 1-5 parts of an inhibitor, and 300-500 parts of a solvent.

[0006] Preferably, the first heat-conductive filler has a tubular microstructure, the second heat-conductive filler has a flake microstructure, and the third heat-conductive filler has a spherical microstructure.

[0007] Preferably, the first thermally conductive filler is a modified single-walled carbon nanotube paste, which is prepared by the following method:

[0008] Mix 1-5 parts of single-walled carbon nanotubes and 100 parts of vinyl silicone oil by weight, stir at 10-20 rpm and less than 35°C for 0.5-2 hours, add 1-4 parts of vinyltrimethoxysilane dropwise while stirring, stir for 5-30 minutes, then add 0.25-1 parts of deionized water and 0.1-0.4 parts of dibutyltin dilaurate dropwise, and continue stirring for 1-4 hours to obtain a modified single-walled carbon nanotube paste.

[0009] Preferably, the first thermally conductive filler is a modified single-walled carbon nanotube paste, which is prepared by the following method:

[0010] Mix 1-5 parts of single-walled carbon nanotubes and 100 parts of vinyl silicone oil by weight, stir at 10-20 rpm and less than 35°C for 1 hour, add 2 parts of vinyltrimethoxysilane dropwise while stirring, stir for 10 minutes, then add 0.5 parts of deionized water and 0.2 parts of dibutyltin dilaurate dropwise, and continue stirring for 2 hours to obtain a modified single-walled carbon nanotube paste;

[0011] The diameter of a single-walled carbon nanotube is 1-2 nm, and the length of a single-walled carbon nanotube is 50-100 μm.

[0012] Preferably, the second thermally conductive filler is one or both of single-layer graphene and boron nitride, wherein the particle size of the single-layer graphene is 2-10 μm, and the particle size of the boron nitride is 5-15 μm.

[0013] Preferably, the third thermally conductive filler is one or more of aluminum nitride, boron nitride, and silicon carbide, wherein the particle size of aluminum nitride is 0.5-5 μm, the particle size of aluminum oxide is 0.5-5 μm, and the particle size of silicon carbide is 0.5-5 μm.

[0014] Preferably, the weight average molecular weight of the vinyl silicone rubber is 400,000-900,000, and the vinyl content is 0.03 wt%-0.20 wt%.

[0015] Preferably, the MQ ratio of the methyl MQ silicone resin is 0.6-0.9, and the weight average molecular weight is 2000-10000.

[0016] Preferably, the catalyst is a platinum catalyst, the inhibitor is butynol, and the solvent is one or more of toluene, ethyl acetate, butanone, and isopropanol.

[0017] A second aspect of the present invention provides a method for preparing the above-mentioned high thermal conductivity buffer type silicone pressure-sensitive adhesive, comprising the following steps:

[0018] Add the solvent and methyl MQ silicone resin into a stirring kettle and stir until completely dissolved. Add vinyl silicone rubber and stir until completely dissolved. Add hydrogenated silicone oil, inhibitor, first thermal conductive powder, second thermal conductive powder and third thermal conductive powder and stir until uniformly mixed. Add the catalyst and stir. Apply the obtained rubber compound with a scraper and vulcanize to obtain a high thermal conductive buffer type silicone pressure sensitive adhesive.

[0019] The beneficial effects of the present invention are:

[0020] The present invention provides a highly thermally conductive, buffered silicone pressure-sensitive adhesive and a preparation method thereof. The silicone pressure-sensitive adhesive provided by the present invention has excellent buffering and thermal conductivity effects and is used in 3C electronics, especially in the structural layer under display screens. After being bonded to copper foil, it can significantly improve heat diffusion and extend the life of electronic components.

[0021] Conventional silicone pressure-sensitive adhesives have a thermal conductivity of approximately 0.2W / (m·K). Conventional methods of adding thermally conductive materials, with limited addition amounts, significantly thicken the adhesive. When the viscosity is too high, it cannot be properly leveled and coated. Furthermore, due to its independent microstructure, it is difficult to establish a good "thermal conduction path," which greatly reduces the thermal conductivity. Under these limitations, the thermal conductivity limit is generally only around 0.5W / (m·K). The present invention employs two special treatments to address this issue. First, surface treatment is performed on the thermally conductive filler that significantly thickens the adhesive. After treatment, a larger amount can be added without changing the adhesive viscosity, resulting in a better thermal conductivity. Second, through the compounding of thermally conductive fillers and the use of a "tubular + lamellar + spherical filling" microstructure, the gaps in the thermally conductive material in the adhesive film particle layout after vulcanization can be reduced, achieving a smoother "thermal conduction path" and facilitating heat diffusion.

[0022] The preparation method of the present invention is simple to operate, is conducive to industrial production and promotion, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the principle diagram of the film cushioning rate test;

[0024] Figure 2 This is the principle diagram of the film plane thermal conductivity test;

[0025] Figure 3 This is the principle diagram of the vertical thermal diffusion coefficient test of the film + copper foil structure sample. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below with reference to the embodiments so that those skilled in the art can implement the invention with reference to the description.

[0027] It should be understood that terms such as “having”, “including” and “comprising” used herein do not preclude the existence or addition of one or more other elements or combinations thereof.

[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Materials and reagents used in the following examples are commercially available unless otherwise specified. In the following examples, where specific conditions are not specified, the experiments were conducted under conventional conditions or those recommended by the manufacturer. Reagents and instruments used, where the manufacturer is not specified, are commercially available conventional products.

[0029] The invention provides a high-thermal-conductivity buffer-type organic silicon pressure-sensitive adhesive. The raw materials for preparing the organic silicon pressure-sensitive adhesive comprise the following components in parts by weight: 90-150 parts of vinyl silicone rubber, 180-300 parts of methyl MQ silicone resin, 1.5-15 parts of hydrogenated silicone oil, 30-60 parts of a first thermally conductive filler, 40-80 parts of a second thermally conductive filler, 40-80 parts of a third thermally conductive filler, 1-5 parts of a catalyst, 1-5 parts of an inhibitor, and 300-500 parts of a solvent.

[0030] In a preferred embodiment, the first heat-conductive filler has a tubular microstructure, the second heat-conductive filler has a flake microstructure, and the third heat-conductive filler has a spherical microstructure.

[0031] In a preferred embodiment, the first thermally conductive filler is a modified single-walled carbon nanotube paste, which is prepared by the following method:

[0032] Mix 1-5 parts of single-walled carbon nanotubes and 100 parts of vinyl silicone oil by weight, stir at 10-20 rpm and less than 35°C for 0.5-2 hours, add 1-4 parts of vinyltrimethoxysilane dropwise while stirring, stir for 5-30 minutes, then add 0.25-1 parts of deionized water and 0.1-0.4 parts of dibutyltin dilaurate dropwise, and continue stirring for 1-4 hours to obtain a modified single-walled carbon nanotube paste.

[0033] After surface treatment, single-walled carbon nanotubes are easier to disperse in the adhesive, thereby increasing the addition amount and better improving the thermal conductivity of the pressure-sensitive adhesive.

[0034] In a preferred embodiment, the first thermally conductive filler is a modified single-walled carbon nanotube paste, which is prepared by the following method:

[0035] Mix 1-5 parts of single-walled carbon nanotubes and 100 parts of vinyl silicone oil by weight, stir at 10-20 rpm and less than 35°C for 1 hour, add 2 parts of vinyltrimethoxysilane dropwise while stirring, stir for 10 minutes, then add 0.5 parts of deionized water and 0.2 parts of dibutyltin dilaurate dropwise, and continue stirring for 2 hours to obtain a modified single-walled carbon nanotube paste;

[0036] The diameter of a single-walled carbon nanotube is 1-2 nm, and the length of a single-walled carbon nanotube is 50-100 μm.

[0037] In a preferred embodiment, the second thermally conductive filler is one or both of single-layer graphene and boron nitride, wherein the particle size of the single-layer graphene is 2-10 μm, and the particle size of the boron nitride is 5-15 μm.

[0038] In a preferred embodiment, the third thermally conductive filler is one or more of aluminum nitride, boron nitride, and silicon carbide, wherein the particle size of aluminum nitride is 0.5-5 μm, the particle size of aluminum oxide is 0.5-5 μm, and the particle size of silicon carbide is 0.5-5 μm.

[0039] In a preferred embodiment, the weight average molecular weight of the vinyl silicone rubber is 400,000-900,000, and the vinyl content is 0.03 wt%-0.20 wt%.

[0040] In a preferred embodiment, the MQ ratio of the methyl MQ silicone resin is 0.6-0.9, and the weight average molecular weight is 2000-10000.

[0041] In a preferred embodiment, the catalyst is a platinum catalyst with a platinum content of 5000 ppm.

[0042] In a preferred embodiment, the inhibitor is butynol.

[0043] In a preferred embodiment, the solvent is one or more of toluene, ethyl acetate, butanone, and isopropanol.

[0044] The present invention also provides a method for preparing the above-mentioned high thermal conductivity buffer type silicone pressure-sensitive adhesive, comprising the following steps:

[0045] Add the solvent and methyl MQ silicone resin into a stirring kettle and stir until completely dissolved. Add vinyl silicone rubber and stir until completely dissolved. Add hydrogenated silicone oil, inhibitor, first thermal conductive powder, second thermal conductive powder and third thermal conductive powder and stir until uniformly mixed. Add the catalyst and stir. Apply the obtained rubber compound with a scraper and vulcanize to obtain a high thermal conductive buffer type silicone pressure sensitive adhesive.

[0046] In a preferred embodiment, the method for preparing the high thermal conductivity buffer type silicone pressure sensitive adhesive is characterized by comprising the following steps:

[0047] Add the solvent and methyl MQ silicone resin into a stirring kettle, stir at 500 rpm for 10 minutes until completely dissolved, add vinyl silicone rubber and stir for 1 hour until completely dissolved, add hydrogenated silicone oil, inhibitor, first thermal conductive powder, second thermal conductive powder and third thermal conductive powder and stir for 2 hours until uniformly mixed, add the catalyst and stir for 10 minutes, apply the obtained rubber compound with a scraper, and cure at 150°C for 5 minutes to obtain a high thermal conductive buffer type silicone pressure sensitive adhesive.

[0048] The above is the overall concept of the present invention. Detailed embodiments and comparative examples are provided below to further illustrate the present invention.

[0049] The sources of the main raw materials in the following examples and comparative examples are as follows:

[0050] (A) Vinyl silicone rubber

[0051] code name Manufacturer Brand Vi content wt% Molecular weight A1 Dongjue Silicone 110-0 0.03 800000 A2 Dongjue Silicone 110-1 0.07 480000 A3 Dayi Chemical 110-2 0.17 640000

[0052] (B) Methyl MQ resin

[0053] code name Manufacturer Brand Molecular weight MQ ratio B1 Dayi Chemical DY-MQ102N 5000-6000 0.73 B2 New Four Seas SH-5201 3000-4000 0.82 B3 Xin Jiayi XJY-8205-08 8000-10000 0.75

[0054] (C) Hydrogenated silicone oil

[0055] code name Manufacturer Brand Viscosity H group content wt% C1 Runhe New Materials RH-DH58 50-60 0.05 C2 Runhe New Materials RH-H23 80-100 0.4 C3 Dow Chemical 7028 50-100 1.6

[0056] (D) First thermally conductive filler

[0057] Homemade, preparation method is as follows:

[0058] 3 parts by weight of single-walled carbon nanotube powder and 100 parts of vinyl silicone oil were added to a kneader at a stirring speed of 10-20 rpm. Stirring was started, and the temperature in the kneader was controlled to be less than 35°C. Stirring was continued for 1 hour. After no obvious powder was formed, 2 parts of vinyltrimethoxysilane were added dropwise while slowly stirring. After stirring for 10 minutes, 0.5 parts of deionized water and 0.2 parts of dibutyltin dilaurate were added dropwise. Stirring was continued for 2 hours to obtain a single-walled carbon nanotube paste. The single-walled carbon nanotubes had a diameter of 1-2 nm and a length of 50-100 μm.

[0059] The untreated CNTs below refer to single-walled carbon nanotube powders that are the same as those above, but are not subjected to the above-mentioned modification treatment.

[0060] (E) Second thermally conductive filler

[0061] code name Material Particle size E1 graphene 10um E2 Boron nitride 10um

[0062] (F) Third thermally conductive filler

[0063] code name Material Particle size F1 Alumina 3um F2 Aluminum nitride 2um F3 Silicon carbide 800nm

[0064] Other additives

[0065]

[0066]

[0067] Examples 1-3 and Comparative Examples 1-3 provide silicone pressure-sensitive adhesives with different raw material ratios. The following are the specific ingredients (in parts by weight) of each example and comparative example:

[0068] Components Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Vinyl silicone rubber A3 90 A2 120 A1 150 A1 150 A1 150 Methyl MQ resin B3 180 B1 240 B2 300 B2 300 B2 300 Hydrogen silicone oil C1 15 C2 5 C3 1.5 C3 1.5 C3 1.5 Untreated CNT / / / / 1.8 The first thermally conductive filler 30 45 60 / / Second thermally conductive filler 40 60 80 / / The third thermal conductive filler 40 60 80 / / catalyst G 5 G 3 G 1 G 1 G 1 inhibitors H 5 H 3 H1 H1 H1 Toluene 300 400 500 500 500

[0069] Components Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Vinyl silicone rubber A1 150 A1 150 A1 150 A1 150 A1 150 A1 150 Methyl MQ resin B2 300 B2 300 B2 300 B2 300 B2 300 B2 300 Hydrogen silicone oil C3 1.5 C3 1.5 C3 1.5 C3 1.5 C3 1.5 C3 1.5 Untreated CNT / / / / / / The first thermally conductive filler 60 / / 60 60 / Second thermally conductive filler / 80 / 80 / 80 The third thermal conductive filler / / 80 / 80 80 catalyst G 1 G 1 G 1 G 1 G 1 G 1 inhibitors H1 H1 H1 H1 H1 H1 Toluene 500 500 500 500 500 500

[0070] The preparation methods of Examples 1-3 and Comparative Examples 1-4 are the same, and all include the following steps:

[0071] Add the solvent and methyl MQ silicone resin into a stirring kettle, stir at 500 rpm for 10 minutes until completely dissolved, add vinyl silicone rubber and stir for 1 hour until completely dissolved, add hydrogenated silicone oil, inhibitor, first thermal conductive filler, second thermal conductive filler and third thermal conductive filler, stir for 2 hours until uniformly mixed, add catalyst and stir for 10 minutes, apply the obtained rubber compound with a scraper, and cure at 150°C for 5 minutes to obtain a high thermal conductive buffer type silicone pressure sensitive adhesive.

[0072] Sample test items are as follows:

[0073] Test items Test equipment Equipment brand Film-steel peeling strength Universal tensile machine INSTRON Film buffer absorption rate Falling ball cushioning equipment Kejian Instruments Film thermal conductivity Thermal conductivity meter XIATECH Thermal diffusion coefficient of film + copper foil Laser scattering instrument BECKMAN COULTER

[0074] Test sample description: Film thickness is 100μm;

[0075] Adhesive film + copper foil structure: 100μm adhesive film laminated on 35μm copper foil.

[0076] Test method description:

[0077] 1. Film-steel peeling strength: Tested according to ASTM-D3330.

[0078] 2. Film cushioning rate:

[0079] Use an 11.2g stainless steel ball to impact the sensor platform from a height of 5.5cm, and record the force value as F1;

[0080] Place the film flat on the sensor platform and impact it with the same falling ball from the same height, recording the force value as F2;

[0081] Calculate the buffer absorption rate: (F1-F2) / F1*100%.

[0082] 3. Film plane thermal conductivity:

[0083] Stack 4 layers of 100μm film with a total thickness of 400um. A sample on the top and bottom is clamped to the temperature sensor (probe) for testing. The instrument calculates the output thermal conductivity based on the heat collected by the probe.

[0084] 4. Vertical thermal diffusion coefficient of film + copper foil:

[0085] The sample is obtained by attaching the adhesive film to the copper foil. The laser is directed to the adhesive film of the sample. The infrared detector collects the heat from the back of the other copper foil. The instrument outputs the thermal diffusion coefficient based on the collected heat. Figure 3 shown.

[0086] The test results are shown in Tables 1 and 2 below:

[0087] Table 1 compares the film performance test results of Examples 1-3 and Comparative Examples 1-4 as follows:

[0088]

[0089] Test items Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Steel plate peeling force gf / in 1725 1647 1698 1635 1728 1605 Buffer absorption rate% 58.8 59.1 58.3 57.6 58.8 58.9 Thermal conductivity W / (m·K) 0.2275 0.6855 0.4532 0.6934 0.3865 0.8124

[0090] Table 2 compares the performance test results of the film + copper foil of Examples 1-3 and Comparative Examples 1-4 as follows:

[0091]

[0092] From the comparison of Table 1 and Table 2, it can be found that: in Comparative Example 1, no thermal conductive material is added, and the thermal conductivity effect is negligible; compared with Comparative Example 2 and Comparative Example 3, the first thermal conductive filler is not surface treated, and it is difficult to implement dispersed addition with the same addition amount; Comparative Example 3 only adds the first thermal conductive filler, and the thermal conductivity effect in the plane direction is not significantly increased, while the thermal conductivity effect in the vertical direction is significantly increased. The tubular thermal conductive material is more inclined to be "obliquely inserted" and dispersed in the adhesive layer, and its 50-100um tube length can meet the thermal conductivity path in the vertical direction; Comparative Example 4 only adds the second thermal conductive filler, and the thermal conductivity effect in the plane direction is significantly improved, but the thermal conductivity effect in the vertical direction is poor, and the sheet thermal conductive material is more inclined to be "flat-laid". " is dispersed in the adhesive layer, which can meet the heat conduction path in the planar direction; in Comparative Example 5, only the third thermally conductive filler is added, and the thermal conductivity effects in the planar and vertical directions are improved, but the improvement is limited. The spherical thermally conductive filler is "filled" in the adhesive layer, which can meet the heat conduction paths in the planar and vertical directions. However, the amount of spherical thermally conductive filler added is limited and its own thermal conductivity is general, so the improvement of the thermal conductivity effect of the film is limited; further Comparative Examples 6-8, two types of thermally conductive fillers are added respectively. When there is a tubular filler, the vertical direction thermal conductivity will be significantly improved. When there is a flake filler, the planar direction thermal conductivity will be significantly improved. When there is a spherical filler, the thermal conductivity effect will be further improved. Examples 1-3 adopt the combination mode of "tubular + flake + spherical", establish heat conduction paths in all directions, and fill the gaps in the paths, thereby achieving excellent thermal conductivity.

[0093] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A high thermal conductivity buffer type silicone pressure sensitive adhesive, characterized in that: The raw materials for its preparation include the following components by weight: 90-150 parts of vinyl silicone rubber, 180-300 parts of methyl MQ silicone resin, 1.5-15 parts of hydrogenated silicone oil, 30-60 parts of a first heat-conducting filler, 40-80 parts of a second heat-conducting filler, 40-80 parts of a third heat-conducting filler, 1-5 parts of a catalyst, 1-5 parts of an inhibitor, and 300-500 parts of a solvent.

2. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 1, characterized in that: The first heat-conductive filler has a tubular microstructure, the second heat-conductive filler has a flake microstructure, and the third heat-conductive filler has a spherical microstructure.

3. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 2, characterized in that: The first thermally conductive filler is a modified single-walled carbon nanotube paste, which is prepared by the following method: Mix 1-5 parts of single-walled carbon nanotubes and 100 parts of vinyl silicone oil by weight, stir at 10-20 rpm and less than 35°C for 0.5-2 hours, add 1-4 parts of vinyltrimethoxysilane dropwise while stirring, stir for 5-30 minutes, then add 0.25-1 parts of deionized water and 0.1-0.4 parts of dibutyltin dilaurate dropwise, and continue stirring for 1-4 hours to obtain a modified single-walled carbon nanotube paste.

4. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 3, characterized in that: The first thermally conductive filler is a modified single-walled carbon nanotube paste, which is prepared by the following method: Mix 1-5 parts of single-walled carbon nanotubes and 100 parts of vinyl silicone oil by weight, stir at 10-20 rpm and less than 35°C for 1 hour, add 2 parts of vinyltrimethoxysilane dropwise while stirring, stir for 10 minutes, then add 0.5 parts of deionized water and 0.2 parts of dibutyltin dilaurate dropwise, and continue stirring for 2 hours to obtain a modified single-walled carbon nanotube paste; The diameter of a single-walled carbon nanotube is 1-2 nm, and the length of a single-walled carbon nanotube is 50-100 μm.

5. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 2, characterized in that: The second thermally conductive filler is one or both of single-layer graphene and boron nitride, wherein the particle size of the single-layer graphene is 2-10 μm, and the particle size of the boron nitride is 5-15 μm.

6. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 2, characterized in that: The third thermal conductive filler is one or more of aluminum nitride, boron nitride, and silicon carbide, wherein the particle size of aluminum nitride is 0.5-5 μm, the particle size of aluminum oxide is 0.5-5 μm, and the particle size of silicon carbide is 0.5-5 μm.

7. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 1, characterized in that: The weight average molecular weight of the vinyl silicone rubber is 400,000-900,000, and the vinyl content is 0.03 wt %-0.20 wt %.

8. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 1, characterized in that: The MQ ratio of the methyl MQ silicone resin is 0.6-0.9, and the weight average molecular weight is 2000-10000.

9. The high thermal conductivity buffer type silicone pressure sensitive adhesive according to claim 1, characterized in that: The catalyst is a platinum catalyst, the inhibitor is butynol, and the solvent is one or more of toluene, ethyl acetate, butanone, and isopropanol.

10. A method for preparing the high thermal conductivity buffer type silicone pressure sensitive adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add the solvent and methyl MQ silicone resin into a stirring kettle and stir until completely dissolved. Add vinyl silicone rubber and stir until completely dissolved. Add hydrogenated silicone oil, inhibitor, first thermal conductive powder, second thermal conductive powder and third thermal conductive powder and stir until uniformly mixed. Add the catalyst and stir. Apply the obtained rubber compound with a scraper and vulcanize to obtain a high thermal conductive buffer type silicone pressure sensitive adhesive.